WIRETAPPING IN THE DIGITAL AGE: SURVEILLANCE CHALLENGES TO PERSONAL DATA PROTECTION IN INDONESIA - Gunawan Widjaja; Adrian Bima Putra (ADISAM PUBLISHER, 2025)
The development of digital technology has brought convenience in information exchange, but also increased the risk of wiretapping and violation of personal data in Indonesia. This research aims to examine the challenges of monitoring wiretapping practices in the context of personal data protection in Indonesia through a literature study of relevant regulations, cases, and literature. The results of the study show that regulatory fragmentation, the absence of independent oversight institutions, weak oversight mechanisms, and low public digital literacy are the main obstacles in protecting personal data from the threat of wiretapping. In addition, the rapid development of technology and cross-border jurisdictional issues complicate monitoring efforts. Regulatory harmonisation, the establishment of effective supervisory institutions, and multi-sector collaboration are needed to strengthen personal data protection in the digital era. This research recommends surveillance system reform, public education, and technical capacity building as strategic steps to create a safe and trusted digital ecosystem in Indonesia